Effects of Methanolic Jatropha multifida L. Extract in Wound Healing Assessed by the Total Number of PMN Leukocytes and Fibroblasts - Juniarti, Juniarti; Aryenti, Aryenti; Yuhernita, Yuhernita; Poerwaningsih, Ernie Ernie (UI Scholars Hub, 2012)
The aim of this study was to evaluate the effects of methanol extract of Jatropha multifida leaves on the wound healing process and to investigate the wound healing activity based on reduced numbers of PMN (polymorpho nuclear) leukocytes and increased numbers of fibroblasts. Methanol extract of dried leaves of J. multifida was used in the wound healing activity studies. The study subjects were 36 white male Sprague Dawlay rats aged 2 months with 150-200 gram body weight. The subjects were divided into 4 groups and experimentally injured: Group I (negative control) underwent injury without subsequent treatment; group II (positive control) received topical treatment with Bethasone-N after injury; group III (solvent control) was treated with 70% methanol; group IV (treatment group) was treated with 10 mg methanol extract of J. multifida Each group consisted of 3 rats, which were decapitated on days 3, 6, and 13 after the start of treatment. Histological preparation was stained with hematoxyline-eosin (HE) and was continuously examined by counting the numbers of PMN leukocytes and fibroblasts as indicators of wound healing on days 3, 6, and 13 of treatment. The study showed lower numbers of PMN leukocytes in subjects treated with the extract of J. multifida as compared to the other groups. The numbers of fibroblasts were significantly higher on days 6 and 13 of treatment. The treatment of injuries with methanol extract of leaves from J. multifida provided better results compared to the other groups in our study.